A numerical method for fractional Biswas-Milovic equation with m = 4 - Körpınar, Zeliha; İnç, Mustafa (AMER SCIENTIFIC PUBLISHERS, 2018)
In this article, numerical solutions of the fractional Biswas-Milovic equation with m = 4, which defines the long-space optical communications, are obtained by using the residual power series method (RPSM). The RPSM also helps to obtain Maclaurin expansion of the solution. Solutions of this equation are computed via convergent series and its representations are given by using the Mathematica software package. Explanations and consequences of the method are presented by graphical models. It is finally shown that this technique is an efficient method for the solution of the fractional Biswas-Milovic equation.
Keywords: Residual Power Series Method; Biswas-Milovic Equation; Series Solution